Use of specular microscopy to determine corneal endothelial cell morphology and morphometry in enucleated cat eyes - Franzen, Angela A. [UNESP]; Pigatto, Joao A. T.; Abib, Fernando Cesar; Albuquerque, Luciane; Laus, Jose L. [UNESP] (Wiley-Blackwell, 2010)
The purpose of this study was to investigate the effect of age on endothelial morphology and morphometry in cats. The corneal endothelium was studied using a contact specular microscope. A total of 18 cats (Felis catus Linnaeus, 1758) were evaluated in this study. The subjects were divided into three groups of six cats each in function of age: G1 (1 to 3 months old), G2 (5 to 12 months old), and G3 (24 to 40 months old). The examination presented data as endothelial cell density (ECD), average cell area, corneal thickness, polymegathism, and pleomorphism. Results revealed ECD decrease in corneas of normal cats with age, as well as a corresponding increase in endothelial cell area and pleomorphism. The present work suggests that the endothelial parameters evaluated change with advancing age.
Keywords: Cat; Cornea; endothelium; Specular microscopy